(untitled) - Maier, Pauline (New York, 2003)
Representing a fresh approach to the teaching of American history, this textbook takes innovation as its theme. The book is a chronological survey, highlighting the ways in which the constant invention of ideas, the impulse to improve, the renewal of old practices in areas as diverse as the American railroad and the rise of jazz, have all animated the progress of American history. The text links the theme of innovation to political, economic, social and cultural developments.
Keywords: Nước Mỹ; Lịch sử